The Up-regulation of TNF-α Maintains Trigeminal Neuralgia by Modulating MAPKs Phosphorylation and BKCa Channels in Trigeminal Nucleus Caudalis - Lu, Zhan-ying; Fan, Juan; Yu, Li-hua; Ma, Bei; Cheng, Li-ming (Frontiers in Cellular Neuroscience, 2021)
Trigeminal neuralgia (TN) is a severe chronic neuropathic pain. Despite numerous available medical interventions, the therapeutic effects are not ideal. To control the pain attacks, the need for more contemporaneous drugs continues to be a real challenge. Our previous study reported that BKCa channels modulated by mitogen-activated protein kinases (MAPKs) in the trigeminal ganglia (TG) neurons play crucial roles in regulating trigeminal neuralgia, and some researches demonstrated that inflammatory cytokine TNF-α could promote neuropathic pain. Meanwhile, trigeminal nucleus caudalis (TNC), the ﬁrst central site of trigeminal nociceptive pathway, is responsible for processing sensory and pain signals from peripheral orofacial area. Thus, the aim of this study is to further investigate whether TNF-α and MAPKs phosphorylation in the TNC could mediate the pathogenesis of trigeminal neuralgia by modulating BKCa channels. The results showed that TNF-α of TNC region is upregulated significantly in the chronic constriction injury of infraorbital nerve (ION-CCI) rats model, which displayed persistent facial mechanical allodynia and hyperalgesia. The normal rats with target injection of exogenous TNF-α to the fourth brain ventricle behaved just like ION-CCI model rats. The fire of action potential of TNC neurons and MAPKs phosphorylation increased accordingly. U0126 and SB203580, which are two MAPKs’ inhibitors and injected to the ION-CCI model rats in the same manner respectively, could attenuate the facial mechanical allodynia and action potential of TNC neurons induced by TNF-α obviously. In addition, the BKCa currents were also recovered after the administration of MAPKs’ inhibitors. Taken together, our work suggests that the up-regulation of TNF-α in TNC region would cause the increase of MAPKs phosphorylation and then the negative regulation of BKCa channels, resulting in the trigeminal neuralgia.